Editorial - Noor, Noraini M. (International Islamic University Malaysia, 2010)
One objective of Intellectual Discourse is to engage scholars in dialogue on Islam and other faiths. This is much needed especially after the incidents of September 11, 2001 which have further heightened the hostility of the West towards Islam......